Cute baby costumes birds: insects reptiles & dinosaurs with interesting & educative rhymes - Dreamland; Dreamland (New Delhi Dreamland Publication, 2003)
This book will teach Signs Of The Zodiac to the young one in a way that is fun and enjoyable and educative. This book is different for it is full of cute looking babies made up to represent different zodiac signs along with information about each sign. But this is not all. Each sign of the zodiac is introduced with a short rhyme, describing its main characteristics. This will not only make remembering them easier but also adds ingenuity and fun to whole process of learning.? The large, colourful pictures of cute and cuddly babies - some laughing, some looking serious, others making faces, but all looking absolutely adorable - staring at you from every page will also make teaching a pleasurable experience.
Keywords: Text book; Birds